2018
DOI: 10.1016/j.pharmthera.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The immature electrophysiological phenotype of iPSC-CMs still hampers in vitro drug screening: Special focus on I K1

Abstract: Preclinical drug screens are not based on human physiology, possibly complicating predictions on cardiotoxicity. Drug screening can be humanised with in vitro assays using human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs). However, in contrast to adult ventricular cardiomyocytes, iPSC-CMs beat spontaneously due to presence of the pacemaking current I and reduced densities of the hyperpolarising current I. In adult cardiomyocytes, I finalises repolarisation by stabilising the resting membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 107 publications
5
110
0
Order By: Relevance
“…[1][2][3][4] In general, it is challenging to study ion-channels in iPSCs due to the lack or low level of expression but we have used the powerful tool of stem cell technology to analyze the pathophysiology of LCA16. 29 The LCA16 mutation p.Trp53* analyzed in this report is a tryptophan (UGG) to amber (UAG) stop codon variant. 1 An in-frame nonsense mutation accounts for about 12% of inherited genetic disorder.…”
Section: Discussionmentioning
confidence: 84%
“…[1][2][3][4] In general, it is challenging to study ion-channels in iPSCs due to the lack or low level of expression but we have used the powerful tool of stem cell technology to analyze the pathophysiology of LCA16. 29 The LCA16 mutation p.Trp53* analyzed in this report is a tryptophan (UGG) to amber (UAG) stop codon variant. 1 An in-frame nonsense mutation accounts for about 12% of inherited genetic disorder.…”
Section: Discussionmentioning
confidence: 84%
“…The third pillar of the CiPA initiative proposes to employ in vitro hiPSC-CMs to confirm the effects of a novel drug predicted by a comprehensive in silico model. hiPSC-CMs and adult ventricular CMs show qualitatively consistent responses to some, but not all drugs (9,20,30). Recently, two computational studies (8,31) quantitatively reported on the main electrophysiological differences between hiPSC-CM and adult ventricular CMs by comparing the Paci 2013 and O'Hara-Rudy models.…”
Section: Toward a Mature Electrophysiological Phenotypementioning
confidence: 99%
“…In adult atrial and ventricular CMs, the resting potential is determined primarily by I K1 (Miake, Marbán, & Nuss, ; Silva & Rudy, ), but low I K1 and lack of channel expression are hallmarks of the immaturity of hPSC‐CMs (Goversen, van der Heyden, van Veen, & de, ). K ir 2.1 could be detected in our hESC‐CMs after 25 days in culture, with a significant increase of expression at 75 days.…”
Section: Discussionmentioning
confidence: 99%